Feeling Oneself Requires Embodiment: Insights From the Relationship Between Own-Body Transformations, Schizotypal Personality Traits, and Spontaneous Bodily Sensations - Michael, George A.; Guyot, Deborah; Tarroux, Emilie; Comte, Mylène; Salgues, Sara (Frontiers in Psychology, 2020)
Subtle bodily sensations such as itching or fluttering that occur in the absence of any external trigger (i.e., spontaneous sensations, or SPS) may serve to locate the spatial boundaries of the body. They may constitute the normal counterpart of extreme conditions in which body-related hallucinations and perceptual aberrations are experienced. Previous investigations have suggested that situations in which the body is spontaneously experienced as being deformed are related to the ability to perform own-body transformations, i.e., mental rotations of the body requiring disembodiment. We therefore decided to consider whether the perception of SPS might relate to embodiment as assessed through (i) the ability to perform own-body transformations (OBT task) and (ii) schizotypal traits (Schizotypal Personality Questionnaire, or SPQ), since high degrees of schizotypy in the general population have been associated with more vivid perceptions and aberrant perceptual experiences. Then participants completed a standard SPS task. Our analysis revealed that the slower the response time in the OBT task, the more frequent the perception of SPS. This suggests that difficulties in disembodying and mentally transforming one’s own body facilitate feeling oneself. Furthermore, a greater number of correct responses in the OBT task was associated with less frequent perception of SPS. This suggests that finding it easier to disembody and perform mental own-body transformations interferes with the ability to sense oneself. The results also show that higher schizotypal traits, as assessed through the SPQ, are associated with more frequent perception of SPS. Taken together, these results provide a coherent picture and suggest that embodiment is required in order to correctly feel oneself, as expressed through the perception of SPS. The ability to easily experience disembodiment reduces the sense of feeling oneself, and proneness to schizotypal traits produces body misperceptions that enhance and amplify this feeling. The results are discussed in the light of current knowledge and theories about body representations, taking into account attention and interoception as factors that influence body awareness. We offer explanations for perceptual aberrations, body-related delusions, and hallucinations based on misperceived or misinterpreted SPS, and we discuss possible mechanisms that may contribute to feeling and misperceiving oneself.